New 2-D silver(I) coordination network constructed from thiomethyl group-substituted p-tert-butylthiacalix[4]arene - Kilic, Huriye Akdas; Graf, Ernest; Hosseini, Mir Wais; Kyritsakas, Nathalie (Tubitak Scientific & Technological Research Council Turkey, 2022)
New ligand based on p-tertbutyltetrathiacalix[4]arene blocked in 1,3-alternate conformation, was achieved via a multistep synthesis with the introduction of thiomethylpropoxy groups on the lower rim which leads to a neutral tecton. The combination of this p-tertbutyltetrathiacalix[4]arene (p-TCA-2), in 1, 3-alternate imposed conformation, with tetrahedral Ag(I)SbF6 salt, leads to the formation of neutral, new 2-D coordination network, which was structurally investigated in the solid state by X-ray diffraction methods on a single crystal.
Keywords: Molecular networks; coordination polymer; thiacalix[4]arene; X-ray structure; thioether; MOLECULAR TECTONICS; THIACALIXARENES; FRAMEWORKS; COMPLEXES; POLYMERS; DESIGN; Chemistry; Engineering